Sea level fluctuations and their signature in the composition and structure of polygonal wedge ice in the Yenisei River lower reaches - O. Opokina L.; E. Slagoda A.; I. Tomberg B.; M. Suslova Yu.; A. Firsova D.; T. Khodzher V.; N. Zhuchenko A.; О. Опокина Л.; Е. Слагода А.; И. Томберг В.; М. Суслова Ю.; А. Фирсова Д.; et al. (Ice and Snow, 2015)
Late Pleistocene and Holocene polygonal-wedge ice is studied in the lower course of the Yenisei River. Ice distribution, features of the formation, chemical and microbiological composition were determined. It was established that ice wedges were formed on the slopes of the depression, in coastal-marine lagoons and in thermokarst during Holocene. The evidence of thermoabrasion and thermokarst in sediments as well as the marine signal in composition of polygonal-wedge ice allowed clarifying the southern limit of the Holocene transgression. В низовьях р. Енисей изучены сартанские и голоценовые полигонально-жильные льды и вмещающие отложения. Проведён анализ их химического и микробиологического состава. Установлено, что голоценовые полигонально-жильные льды формировались в разных условиях: на склонах депрессий; в мелководных прибрежно-морских лагунах; на первой морской террасе; в термокарстовых понижениях. Показано, что осадконакопление и рост полигонально-жильных льдов в низовьях р. Енисей коррелирует с уровнем моря в голоцене.